Gain enhancement of octagon microstrip Yagi antenna utilizing 1-D photonic crystal (PCs) cover - Muhammad Chatib Quzwain, Kamelia; Ismail, Alyani; Sali, Aduwati; Alhawari, Adam Reda Hasan (2015)
A high gain Octagon Microstrip Yagi Antenna (OMYA) for Worldwide Interoperability for Microwave Access (WiMAX) application at unlicensed frequency of 5.8 GHz is presented in this paper. The proposed antenna was simulated and optimized using full-wave EM simulator. The simulated results show that the gain of the proposed antenna at frequency of 5.8 GHz is 13.45 dB with S11 of -32.57 dB. Hence, an extra gain of about 5.47 dB can be obtained through this design.